Representation of Cone-Opponent Color Space in Macaque Early Visual Cortices - Du, Xiao; Jiang, Xinrui; Kuriki, Ichiro; Takahata, Toru; Zhou, Tao; Roe, Anna Wang; Tanigawa, Hisashi (Frontiers in Neuroscience, 2022)
In primate vision, the encoding of color perception arises from three types of retinal cone cells (L, M, and S cones). The inputs from these cones are linearly integrated into two cone-opponent channels (cardinal axes) before the lateral geniculate nucleus (LGN). In subsequent visual cortical stages, color-preferring neurons cluster into functional domains within ‘blobs’ in V1, ‘thin/color stripes’ in V2, and ‘color bands’ in V4. Here, we hypothesize that, with increasing cortical hierarchy, the functional organization of hue representation becomes more balanced and less dependent on cone opponency. To address this question, we used intrinsic signal optical imaging in macaque V1, V2, and V4 cortices to examine the domain-based representation of specific hues (here referred to as ‘hue domains’) in cone-opponent color space (4 cardinal and 4 intermediate hues). Interestingly, we found that in V1, the relative size of S-cone hue preference domain was significantly smaller than that for other hues. This notable difference was less prominent in V2, and, in V4 was virtually absent, resulting in a more balanced representation of hues. In V2, hue clusters contained sequences of shifting preference, while in V4 the organization of hue clusters was more complex. Pattern classification analysis of these hue maps showed that accuracy of hue classification improved from V1 to V2 to V4. These results suggest that hue representation by domains in the early cortical hierarchy reflects a transformation away from cone-opponency and towards a full-coverage representation of hue.